Strategi Pemasaran Digital dalam Meningkatkan Loyalitas Konsumen: Studi pada UMKM di Era Industri 4.0 - Sitindaon, Nikson (STIE Bina Karya, 2025)
The development of technology in the Industry 4.0 era has encouraged Micro, Small, and Medium Enterprises (MSMEs) to adopt digital marketing strategies in carrying out their business activities. This study aims to analyze how digital marketing strategies can increase consumer loyalty in MSMEs, especially through the use of social media, e-commerce, and digital-based customer relationship management (CRM). The research method used is qualitative with a case study approach on several MSMEs that are actively conducting digital marketing. The results of the study show that the implementation of digital strategies such as attractive marketing content, active interaction with customers on online platforms, and proper use of customer data has been proven to increase consumer engagement and loyalty. This study concludes that digital marketing is not only a promotional tool, but also a strategy for building long-term relationships with consumers that are effective and relevant in the current era of digital transformation.